2003
DOI: 10.1111/j.1471-4159.2003.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of calcium release from the endoplasmic reticulum could only provide partial neuroprotection against beta‐amyloid peptide toxicity

Abstract: Beta-amyloid (Ab) peptide has been suggested to play important roles in the pathogenesis of Alzheimer's disease (AD). Ab peptide neurotoxicity was shown to induce disturbance of cellular calcium homeostasis. However, whether modulation of calcium release from the endoplasmic reticulum (ER) can protect neurons from Ab toxicity is not clearly defined. In the present study, Ab peptide-triggered ER calcium release in primary cortical neurons in culture is modulated by Xestospongin C, 2-aminoethoxydiphenyl borate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 67 publications
(102 reference statements)
4
27
0
Order By: Relevance
“…Although it is unclear how extracellular Aβ signals to the ER, it has been shown that extracellular Aβ can induce the UPR [66,67] (data reproduced in our lab, Chafekar and Scheper, unpublished). Aβ induces Ca 2+ release from the ER [68] and inhibition of Ca 2+ release, which concomitantly attenuates the upregulation of BiP, partly relieves Aβ toxicity [66].…”
Section: A Role For Presenilin In Upr Signalingsupporting
confidence: 54%
See 1 more Smart Citation
“…Although it is unclear how extracellular Aβ signals to the ER, it has been shown that extracellular Aβ can induce the UPR [66,67] (data reproduced in our lab, Chafekar and Scheper, unpublished). Aβ induces Ca 2+ release from the ER [68] and inhibition of Ca 2+ release, which concomitantly attenuates the upregulation of BiP, partly relieves Aβ toxicity [66].…”
Section: A Role For Presenilin In Upr Signalingsupporting
confidence: 54%
“…Aβ induces Ca 2+ release from the ER [68] and inhibition of Ca 2+ release, which concomitantly attenuates the upregulation of BiP, partly relieves Aβ toxicity [66]. In contrast, upregulation of BiP was suggested to be protective in Aβ toxicity [67].…”
Section: A Role For Presenilin In Upr Signalingmentioning
confidence: 97%
“…Diverse studies have demonstrated that A -42 signals to the ER and induces the UPR [164,165]. It has been shown that caspase-12 deficient neurons have reduced sensitivity to A peptide [158].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Disrupted ER Ca 2+ homeostasis has been suggested to have a key role in the pathogenesis of AD (reviewed in [197]). In particular, the ability of Aβ to evoke Ca 2+ leakage from IP 3 and ryanodine receptors in ER has been shown to be involved in the activation of apoptotic death in cells stressed with Aβ peptides [198][199][200].…”
Section: Mitochondria and Endoplasmic Reticulum Dysfunctionmentioning
confidence: 99%